Brand Establishment at the University of Chicago: An Investigation of De-Escalation of Commitment in University Athletics - Adrien Bouchet; Michael Hutchinson (Journal of Applied Sports Management, 2013)
This article is a historical case analysis of the University of Chicago’s decision to discontinue participation in scholarship football in 1939. This decision was made at the behest of then University of Chicago President Robert Hutchins and Board of Trustee members in hopes of preserving the university’s academic reputation and brand. This article discusses the decision of a highly selective and academically prestigious research university to abandon Division I athletics during a period of athletic success by its football team. This unprecedented decision by a founding member of one of the nation’s premier athletic conferences, the Big Ten, has left questions about the role of intercollegiate athletics within a highly selective and academically prestigious university.
Keywords: De-escalation of Commitment; University Branding; Intercollegiate Athletics; University of Chicago